Students’ expectations of, and experiences in e-learning: Their relation to learning achievements and course satisfaction - Paechter, Manuela; Maier, Brigitte; Macher, Daniel (Computers and education, 2010)
Within only a few years, the use of e-learning has increased rapidly in Austria. In certain subjects, up to 60% of university students report using e-learning platforms at least ‘sometimes’ or ‘frequently’ ( Unger & Wroblewski, 2006). Yet, which aspects of e-learning do students consider important for their learning achievements and course satisfaction? This question was addressed by surveying 2196 students from 29 universities in Austria about their expectations of, and experiences in e-learning. Multiple regression analyses using Mplus 4.21 were carried out to investigate how different facets of students’ expectations and experiences are related to perceived learning achievements and course satisfaction. With regard to their expectations, i.e., aspects of a course they consider important, students’ achievement goals were the best predictors for success and ranked higher than other course characteristics. With regard to their experiences, students’ assessments of the instructor’s expertise in e-learning, and her/his counseling and support were the best predictors for learning achievement and course satisfaction. Furthermore, self-regulated and collaborative learning were related to learning achievements. The results of the study suggest to influence students’ motivation and goals by adapting instruction accordingly and emphasize the importance of continuing education and training for the instructors.